2021
DOI: 10.1002/tcr.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Semiconductor Photoelectrochemistry

Abstract: In the field of synthetic organic chemistry, photochemical and electrochemical approaches are often considered to be competing technologies that induce single electron transfer (SET). Recently, their fusion, i. e., the “photoelectrochemical” approach, has become the focus of attention. In this approach, both solar and electrical energy are used in creative combinations. Historically, the term “photoelectrochemistry” has been used in more inorganic fields, where a photovoltaic effect exhibited by semiconducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…Since not only the formation of vinylcyclobutane ( 6) but also that of the cycloadduct ( 5) were observed even in the very early stage, it seems that two pathways, direct and indirect, are possible to construct the six-membered ring. Namely, the radical cation (1 * + ) is first trapped by the diene (3) to form the initial carboncarbon bond and formally generate the distonic radical cation (7). Radical cation (7) can then be cyclized via single electron reduction to form both six-and four-membered rings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since not only the formation of vinylcyclobutane ( 6) but also that of the cycloadduct ( 5) were observed even in the very early stage, it seems that two pathways, direct and indirect, are possible to construct the six-membered ring. Namely, the radical cation (1 * + ) is first trapped by the diene (3) to form the initial carboncarbon bond and formally generate the distonic radical cation (7). Radical cation (7) can then be cyclized via single electron reduction to form both six-and four-membered rings.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, the radical cation (1 * + ) is first trapped by the diene (3) to form the initial carboncarbon bond and formally generate the distonic radical cation (7). Radical cation (7) can then be cyclized via single electron reduction to form both six-and four-membered rings. Although mechanistic aspects remain unclear, single electron oxidation may trigger the rearrangement of the vinylcyclobutane (6) into the cycloadduct (5), which accords well with our previous observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed radical cation cycloadditions using (photo)electrochemical single-electron transfer in lithium per- chlorate (LiClO 4 )/nitromethane (CH 3 NO 2 ) solution [36][37][38][39][40][41][42][43][44]. During the course of our studies, we found that the TiO 2 photoelectrochemical approach was more beneficial than simple electrochemistry in most cases, probably because both single-electron oxidation and reduction are made possible at the same surface [45]. This is especially true for the radical cation Diels-Alder reaction, since non-substituted β-methylstyrene, which was previously reported as an unsuccessful dienophile, was found to participate under TiO 2 photoelectrochemical conditions (Scheme 1) [46,47].…”
Section: Introductionmentioning
confidence: 99%